The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1108/02640471211221377
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of metadata records machine translation

Abstract: Purpose of this paperThe purpose of this study is to evaluate freely available machine translation (MT) services' performance in translating metadata records. Design/methodology/approachRandomly selected metadata records were translated from English into Chinese using Google, Bing, and SYSTRAN Machine Translation (MT) systems. These translations were then evaluated using a five point scale for both Fluency and Adequacy. Missing Count (words not translated) and Incorrect Count (words incorrectly translated) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…This study was one of the very few studies that conducted human evaluation of MT on metadata records. It confirmed the conclusion from the previous study (Chen et al, ) that online MT systems could produce non‐native yet sufficiently good translations that might help information users in many ways overcome language barriers. However, it significantly extended the MT evaluation in our previous study (Chen et al, ) to more languages and a larger sample size.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study was one of the very few studies that conducted human evaluation of MT on metadata records. It confirmed the conclusion from the previous study (Chen et al, ) that online MT systems could produce non‐native yet sufficiently good translations that might help information users in many ways overcome language barriers. However, it significantly extended the MT evaluation in our previous study (Chen et al, ) to more languages and a larger sample size.…”
Section: Discussionsupporting
confidence: 89%
“…It confirmed the conclusion from the previous study (Chen et al, ) that online MT systems could produce non‐native yet sufficiently good translations that might help information users in many ways overcome language barriers. However, it significantly extended the MT evaluation in our previous study (Chen et al, ) to more languages and a larger sample size. Especially, we conducted evaluation on different elements and found that some online MT systems, such as Google Translate and Bing Translator, produced translations with high levels of fluency and adequacy for certain metadata elements such as subject and creator.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The evaluation of different MT services or open source systems for translation of scholarly articles would be useful for international scholars. There is some related research on evaluating MT systems for translation of metadata in digital libraries that would be worth discussing in this context (Chen et al, ; Reyes Ayala et al, ). This gap is partially justified by the complexity of those topics and the limited research on the multilingual aspects of scholarly communication.…”
mentioning
confidence: 99%